STRATEGI PENGEMBANGAN KUALITAS PELAYANAN UNTUK MEMENUHI KEINGINAN KONSUMEN PADA BENGKEL WIJAYA TOYOTA - Anggit Suryopratomo (Universitas Insan Cendekia Mandiri, 2019)
This study addresses the complex problems in taking a decision to achieve corporate objectives, to improve the quality of consumer care services, as well as care services in accordance with the wishes of the customer in Workshop Wijaya Toyota (PT Wijaya Motor Lestari) in partnership with PT Astra International Tbk. This research is descriptive, assigning a sample of 100 customers. Data were processed in the qualitative methods using Quality Function Deployment and the result was displayed in a matrix House of Quality. The results show that strategies the workshop Wijaya Toyota applies to improving the quality of services are: the waiting room and toilet cleanliness, promoting warranty repair workshop, ensuring the accuracy of completion time of maintenance, speed of completion of the work, maintenance appropriate to their complaints, garage attendant explanation of maintenance, stock availability of original spare parts, direct workshop personnel explanation at the time of submission, garage attendant explanation upon delivery, transparent overall cost to be paid, reasonableness price of original parts, friendliness and courtesy officer spare parts, and workshop personnel direct contact.